2020
DOI: 10.1101/2020.04.11.034603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell-Type-Specific Expression of Renin-Angiotensin-System Components in the Human Body and Its Relevance to SARS-CoV-2 Infection

Abstract: We have analyzed the cell-type-specific expression of the renin-angiotensin system (RAS) components across 141 cell types or subtypes as defined by single-cell RNA-seq (scRNAseq) analysis. ACE2, one of the components of RAS, also facilitates SARS-CoV-2 entry into cells in cooperation with its associated protease TMPRSS2. Therefore, our analysis also contributes to the understanding of SARS-CoV-2 infection, spreading of the virus throughout the body, and potential viral interference with RAS in COVID-19 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…ACE2 and TMPRSS2 could help SARS-CoV-2 entry into the human cells, and it has been showed that ACE2 and TMPRSS2 expressions are widely distributed across human tissues including lung, liver, kidney, heart, brain and multiple digestive tract organs [ 28 , 33 , 147 , 148 ]. The co-expression of ACE2 and TMPRSS2 in the intestinal enterocytes may explain the disruption of intestinal absorption that leads to diarrhea [ 38 , 149 ]. Moreover, ACE2 and TMPRSS2 are highly expressed in renal tubular cells, implying that SARS-CoV-2 may directly bind to ACE2-positive cells in the kidney and destroy the function of renal tubules [ 32 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ACE2 and TMPRSS2 could help SARS-CoV-2 entry into the human cells, and it has been showed that ACE2 and TMPRSS2 expressions are widely distributed across human tissues including lung, liver, kidney, heart, brain and multiple digestive tract organs [ 28 , 33 , 147 , 148 ]. The co-expression of ACE2 and TMPRSS2 in the intestinal enterocytes may explain the disruption of intestinal absorption that leads to diarrhea [ 38 , 149 ]. Moreover, ACE2 and TMPRSS2 are highly expressed in renal tubular cells, implying that SARS-CoV-2 may directly bind to ACE2-positive cells in the kidney and destroy the function of renal tubules [ 32 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The co-expression of ACE2 and TMPRSS2 in the intestinal enterocytes may explain the disruption of intestinal absorption that leads to diarrhea [ 38 , 149 ]. Moreover, ACE2 and TMPRSS2 are highly expressed in renal tubular cells, implying that SARS-CoV-2 may directly bind to ACE2-positive cells in the kidney and destroy the function of renal tubules [ 32 , 38 ]. Furthermore, ACE2 and TMPRSS2 were co-expressed in heart, which may be related with the attack of SARS-CoV-2 in heart and lead to cardiac injury in patients with COVID-19 [ 29 , 35 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations